2018
DOI: 10.1097/mcg.0000000000000802
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Bleeding Following Cold Snare Polypectomy for Small Colorectal Polyps in Patients Taking Antithrombotic Agents

Abstract: Colorectal polyps ≤10 mm can be removed without an increase in delayed bleeding using dedicated cold snare polypectomy in patients taking antithrombotic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 16 publications
2
41
0
Order By: Relevance
“…The use of antithrombotics was identified as a significant risk factor for immediate bleeding, which occurred in 63 (5.4%) cases and was readily controlled without any significant clinical consequences. The finding of no cases of DPPB is compatible with several available studies of patients taking antithrombotics without discontinuation prior to polypectomy (Table 1), with rates of DPPB ranging from 0 to 1.2% [4,9,10], lending support to the safety of CSP.…”
supporting
confidence: 85%
“…The use of antithrombotics was identified as a significant risk factor for immediate bleeding, which occurred in 63 (5.4%) cases and was readily controlled without any significant clinical consequences. The finding of no cases of DPPB is compatible with several available studies of patients taking antithrombotics without discontinuation prior to polypectomy (Table 1), with rates of DPPB ranging from 0 to 1.2% [4,9,10], lending support to the safety of CSP.…”
supporting
confidence: 85%
“…In regard to antiplatelet drugs, some recent studies have shown that continuation of clopidogrel was a low-risk factor in CP [15-17]. In our study, there was only one patient taking clopidogrel and no bleeding occurred in that patient.…”
Section: Discussionmentioning
confidence: 54%
“…5 Two studies have specifically looked at CSP on antithrombotics. 22,23 Overall, the risk of delayed postpolypectomy bleeding following CSP was acceptably low, with only 2 of 207 patients on therapeutic antithrombotic agents experiencing delayed postpolypectomy bleeding. Both of these patients were on direct oral anticoagulants (dabigatran and apixaban).…”
Section: Discussionmentioning
confidence: 99%
“…Both of these patients were on direct oral anticoagulants (dabigatran and apixaban). 22,23 Complete resection is now considered a powerful indicator of the quality of colonoscopy. 24 HSP has conventionally been used, which is thought to provide thermal ablation of polyp at the polypectomy margin.…”
Section: Discussionmentioning
confidence: 99%